LEGAL ARRANGEMENTS FOR THE ENFORCEMENT OF THE NEUTRALITY VIOLATION OF THE STATE CIVIL APPARATUS (ASN) IN SIMULTANEOUS REGIONAL HEAD ELECTIONS (CASE STUDY IN SRAGEN REGENCY) - Diyah Nur Widowati (Universitas 17 Agustus 1945 Semarang, 2022)
The State Civil Apparatus (ASN) role is crucial to carry out government affairs within the framework of achieving national goals. In carrying out these duties as a state apparatus, they must provide services to the community in a professional, honest, fair, and equitable manner in carrying out state, government, and development tasks. ASN must be neutral from the influence of all political groups and parties and not discriminate in providing services to the community. In 2015, Sragen Regency participated in celebrating the democratic party, namely the simultaneous election of regional heads and deputy regional heads on December 9, 2015. The Panwaslu (Election Supervisory Committee) of Sragen Regency found and received reports that many ASNs were not neutral. The Panwaslu report reached KASN, and several cases were left without follow-up handling and seemed to evaporate. This study uses qualitative research methods to obtain facts regarding the problem of ASN neutrality in the Sragen Regency in the 2015 simultaneous regional elections. The unit of analysis in this research is the Panwaslu of Sragen Regency and the Education and Training Personnel Agency (BKPP) of Sragen Regency. Data collection techniques used are in-depth interviews and documentation to complete the data in this study. ASN violations occurred before the campaign period and during the campaign period. The number of ASN is not neutral by attending campaigns, other stage activities, and providing campaign materials using state facilities such as office buildings and ASN official vehicles. Of course, the involvement and alignment of ASN in the 2015 Regional Head Elections is due to the incumbent candidate. The Sragen Regency Government, namely the Sragen Regent, should give sanctions or disciplinary punishments to ASN who are not neutral in following the existing laws and regulations. The Sragen Regent should be more firm in responding to this non-neutral ASN case. Legal arrangements are needed to handle ASN Neutrality violations in the General Election and Simultaneous Regional Head Elections.